Meningkatkan Minat Belajar dan Prestasi Mata Pelajaran Ekonomi Materi Perpajakan Menggunakan Cara Pembelajaran Berbasis Masalah - Ririn Kusumawardani (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
Economics lessons method and media is very minimal. This study aims to increase learning interest and achievement in economics subjects by applying the Problem Based Learning (PBL) model. With this PBL model it is expected that students' interest and learning achievement will increase, the score they achieve is complete or minimum KKM is 75. If it is less than 75 then it is not complete. In the pre-cycle, which has not used the PBL learning model, the student's score is 22.22%, where 8 students reached the KKM, and 28 students or 77.78% have not reached the KKM. After learning using the PBL model showed in cycle 1, 66.67% where students who completed were 24 and not completed were 12. In cycle 2 94.44% where students who completed were 34 and not completed were 2. It can be seen that the implementation of class action from each cycle has increased learning outcomes. This increase in learning achievement shows that the application of the PBL method is effectively applied in economics learning. Based on the table of results on students' interest in economics, lessons with the PBL model. In cycle 1 there were 1.85% and in cycle 2 there were 43.52%.